A high-plasticity gadolinium-containing aluminum-based composite material and its preparation method and application

By pretreating and refining the gadolinium oxide powder, combined with thermal isostatic molding and rolling hot deformation processes, the existing gadolinium-containing aluminum-based composite materials are solved, and a composite material with high plasticity and high mechanical properties is achieved, which is suitable for neutron shielding devices.

CN119061284BActive Publication Date: 2025-03-18GRIMAT ENG INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411558034.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The poor plasticity of existing gadolinium-containing aluminum-based composite materials leads to difficulties in processing and forming, and affects the neutron shielding performance.

Method used

Through the pretreatment and refinement of gadolinium oxide powder, combined with thermal isostatic molding and rolling hot deformation processes, the elongation and mechanical properties of the composite material are improved.

Benefits of technology

The elongation, tensile strength and yield strength of the composite material are significantly improved while maintaining a high level of neutron shielding ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119061284B_ABST
    Figure CN119061284B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of particle-reinforced aluminum-based composite materials, and specifically relates to a high-plasticity gadolinium-containing aluminum-based composite material, and its preparation method and application. The present invention transforms the crystal form of gadolinium oxide powder by powder pretreatment, refines the powder particles by ball milling, and then combines hot isostatic pressing and rolling hot deformation processes, thereby significantly improving the comprehensive mechanical properties of the composite material such as elongation while ensuring the thermal neutron shielding ability. The high-plasticity gadolinium-containing aluminum-based composite material (Gd2O3 / 6063Al) prepared by the method disclosed in the present invention has a density greater than 99.5%, a room temperature tensile strength greater than 200MPa, a yield strength greater than 140MPa, and an elongation of 10%-17%. It is a composite material with excellent comprehensive performance and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of particle-reinforced aluminum-based composite materials, and specifically relates to a high-plasticity gadolinium-containing aluminum-based composite material and a preparation method and application thereof. Background Art

[0002] Thermal neutrons, medium neutrons and fast neutrons are released during the storage of spent fuel in nuclear power plants. In recent years, due to the increasing application of nuclear energy, the preparation, basic research and application of thermal neutron shielding materials have attracted widespread attention from researchers at home and abroad. In industry, composite materials prepared with 6xxx series aluminum alloy as the matrix, 30% B4C by mass as the neutron absorber and reinforced particles are mainly used as shielding storage grids. However, when the B4C content is high, the accompanying high hardness makes the processing and forming of the material difficult; reducing the B4C content will lead to a decrease in neutron shielding performance.

[0003] Among all rare earth elements, Gd has the largest thermal neutron absorption cross section and is usually used as a neutron absorber in control rods and a burnable poison treatment agent in nuclear reactors. Its room temperature oxide Gd2O3 can not only generate a ceramic phase with a high elastic modulus through in-situ reaction after ball milling to improve the mechanical properties of composite materials, but also has significant cost advantages compared to other Gd-containing compounds, making it an ideal shielding enhancement phase.

[0004] Patent document CN110643859A uses cold pressing + vacuum sintering to prepare (25W+5Gd2O3) / Al composite materials, and patent document CN11250697B uses spark plasma sintering to prepare (SiC p +Gd2O3) / Al alloy composite material, patent document ZL201510701260.2 uses vacuum hot pressing-hot extrusion method to prepare (15B4C+1Gd2O3) / Al composite material, the materials obtained by the above method have similar shielding properties to industrial 30B4C / Al. However, the Gd2O3 prepared by the above method will produce brittle Al-Gd intermediate phase in situ at the grain boundary, resulting in poor plasticity of the composite material, and the elongation of the finished material is only about 5%, which greatly limits the subsequent design, processing and application of the composite material. Summary of the invention

[0005] In view of the disadvantage of poor plasticity of existing gadolinium-containing aluminum-based composite shielding materials, the present invention provides a high-plasticity gadolinium-containing aluminum-based composite material and a preparation method and application thereof. The present invention specifically includes the following contents:

[0006] A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material comprises the following steps:

[0007] S1, pretreatment of gadolinium oxide powder: heating the cubic gadolinium oxide powder to 1200-1800° C. and keeping the temperature for 0.3-0.8 h to cause a crystal transformation to obtain a monoclinic gadolinium oxide powder;

[0008] S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, ball-milling the monoclinic gadolinium oxide powder, and vacuum drying after the ball-milling to obtain a refined gadolinium oxide powder with a D50 of 1-2 μm;

[0009] S3, composite mixing: the refined gadolinium oxide powder and 6063 aluminum alloy powder are mixed in a mass ratio of (5-15): (85-95) to obtain a mixture, and then the mixture is mixed and ball-milled in an inert gas atmosphere to obtain a gadolinium oxide / 6063 aluminum composite powder;

[0010] S4, cold isostatic pressing: cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to be 50-200 MPa, and holding the pressure for 10-40 min to obtain a cold isostatic pressed ingot;

[0011] S5, hot isostatic pressing and sintering: the cold isostatic pressed ingot is sealed with an aluminum sheath, and then the temperature is raised to 485-520° C. for hot isostatic pressing and sintering, the hot isostatic pressing and sintering pressure is controlled to be 100-200 MPa, and the holding time is 1.5-3 h. After cooling, the aluminum sheath is removed to obtain a hot isostatically pressed aluminum-based composite material containing gadolinium;

[0012] S6, rolling: heating the hot isostatically pressed gadolinium-containing aluminum-based composite material to 450-500°C and keeping the temperature for at least 1 hour, then rolling, controlling the deformation of a single pass to be 15%-20%, keeping the temperature for 5-15 minutes after each rolling pass, and controlling the total deformation to be 50%-90%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

[0013] Furthermore, the purity of the gadolinium oxide powder in step S1 is greater than 99.99%, and D50 is 4-5 μm; and / or, the heating rate in step S1 is 5-15° C. / min; and / or, after the insulation in step S1 is completed, the powder is air-cooled to room temperature.

[0014] Furthermore, in the ball milling of step S2: the mixing mass ratio of monoclinic gadolinium oxide powder to grinding balls is controlled to be 1:(0.8-1.2), the ball milling speed is 250-350 r / min, and the ball milling time is 10-15 h; and / or, the vacuum drying time in step S2 is 8-12 h.

[0015] Furthermore, the purity of the 6063 aluminum powder in step S3 is greater than 99.95%, and D50 is 15-25 μm; and / or, the ball milling in step S3: controlling the mixing mass ratio of the mixture to the grinding balls to be 1:(0.8-1.2), the ball milling speed to be 25-35 r / min, and the ball milling time to be 10-24 h.

[0016] Furthermore, during the cold isostatic pressing in step S4: a rubber sheath is used to isolate the hydraulic medium from the gadolinium oxide / 6063 aluminum composite powder.

[0017] Furthermore, the sealing method in step S5 is as follows: placing the cold isostatically pressed ingot in a prefabricated aluminum package at 350-450°C and a vacuum degree of less than 1×10 -3 Pa; and / or, the heating rate in step S5 is 5-15°C / min; and / or, the cooling method in step S5 is furnace cooling.

[0018] Furthermore, the heating rate in step S6 is 3-7° C. / min; and / or, step S6 is performed by using a two-roll rolling mill, and the number of rolling passes is controlled to be 4-8.

[0019] A high-plasticity gadolinium-containing aluminum-based composite material prepared by the preparation method.

[0020] Furthermore, its elongation is 10%-17%, its density is greater than 99.5%, its room temperature tensile strength is greater than 200 MPa, and its yield strength is greater than 140 MPa.

[0021] An application of the highly plastic gadolinium-containing aluminum-based composite material in a neutron shielding device.

[0022] Beneficial effects of the present invention:

[0023] The present invention transforms the crystal form of gadolinium oxide powder by powder pretreatment, refines the powder particles by ball milling, and combines hot isostatic pressing and rolling thermal deformation processes, thereby significantly improving the comprehensive mechanical properties of the composite material, such as elongation, while ensuring the thermal neutron shielding ability. Specifically, the present invention transforms the crystal form of the reinforcing phase gadolinium oxide powder into a monoclinic crystal form by keeping the reinforcing phase gadolinium oxide powder at a specific temperature for a specific time, and then combines the ball milling refinement technology, on the one hand, the elastic modulus of the reinforcing phase gadolinium oxide is improved (from 126Gpa to 201Gpa), the pinning effect of the reinforcing phase gadolinium oxide particles at the grain boundary is enhanced, and the tensile strength of the hot isostatically pressed material is improved; on the other hand, the density of gadolinium oxide is slightly increased after it is transformed into a monoclinic system, which also has a certain promoting effect on the shielding performance of the material. In addition, the use of a double-cone mixer for mixing can avoid the diffusion of Al atoms into the gadolinium oxide lattice after high-energy ball milling, inhibit the generation of brittle Al-Gd intermediate phase, and improve the mechanical properties of the material; the composite material is subjected to rolling hot deformation treatment to optimize the strength of the aluminum-based composite material while still allowing the material to have a high elongation.

[0024] The high-plasticity gadolinium-containing aluminum-based composite material (Gd2O3 / 6063Al) prepared by the method disclosed in the present invention has a density greater than 99.5%, a room temperature tensile strength greater than 200 MPa, a yield strength greater than 140 MPa, and an elongation of 10%-17%. It is a composite material with excellent comprehensive performance and great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a comparison chart of the thermal neutron transmittance of the high-plasticity gadolinium-containing aluminum-based composite shielding material prepared by the present invention at different thicknesses and monoclinic gadolinium oxide addition amounts and the thermal neutron transmittance of the commonly used industrial aluminum-based composite material containing 30% boron carbide;

[0026] Figure 2 The XRD spectrum (a) and the secondary electron microscopic morphology photograph (b) of the fine gadolinium oxide powder obtained by ball milling in Example 1 of the present invention;

[0027] Figure 3 is a scanning electron microscope microstructure photograph of a cross section of a high-plasticity gadolinium-containing aluminum-based composite material prepared in Example 1 of the present invention;

[0028] Figure 4 This is a scanning electron microscope microstructure photograph of the fracture of the high-plasticity gadolinium-containing aluminum-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments shown below do not limit the invention content described in the claims. In addition, the entire contents of the structures represented by the following embodiments are not limited to those necessary as solutions to the invention described in the claims.

[0030] A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material comprises the following steps:

[0031] S1, pretreatment of gadolinium oxide powder: placing a cubic gadolinium oxide powder with a purity greater than 99.99% and a D50 of 4-5 μm in a muffle furnace, heating it to 1200-1800° C. at a rate of 5-15° C. / min, and keeping it at that temperature for 0.3-0.8 h to cause a crystal transformation, and air-cooling it to room temperature to obtain a monoclinic gadolinium oxide powder with a D50 of 4-5 μm;

[0032] S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, placing the monoclinic gadolinium oxide powder in a high-energy ball mill for ball milling, controlling the mixing mass ratio of the monoclinic gadolinium oxide powder to the grinding ball to be 1:(0.8-1.2), the ball milling speed to be 250-350 r / min, the ball milling time to be 10-15 h, and vacuum drying for 8-12 h after the ball milling to obtain a refined gadolinium oxide powder with a D50 of 1-2 μm;

[0033] S3, composite mixing: the refined gadolinium oxide powder is mixed with 6063 aluminum alloy powder with a purity greater than 99.95% and a D50 of 15-25 μm in a mass ratio of (5-15):(85-95) to obtain a mixture, and then the mixture is mixed and ball-milled in an inert gas (preferably argon) atmosphere using a double cone mixer, and the mixing mass ratio of the mixture to the grinding ball is controlled to be 1:(0.8-1.2), the ball milling speed is 25-35 r / min, and the ball milling time is 10-24 h to obtain a gadolinium oxide / 6063 aluminum composite powder;

[0034] S4, cold isostatic pressing: using a rubber sheath to isolate the hydraulic medium from the gadolinium oxide / 6063 aluminum composite powder, and then cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to be 50-200 MPa, and holding the pressure for 10-40 min to obtain a cold isostatic pressed ingot;

[0035] S5, hot isostatic pressing sintering: the cold isostatic pressed ingot is placed in a prefabricated aluminum package at 350-450°C and a vacuum degree of less than 1×10 -3Pa, and then heat to 485-520°C at a rate of 5-15°C / min for hot isostatic pressing, controlling the hot isostatic pressing pressure to be 100-200MPa and the holding time to be 1.5-3h. After cooling in the furnace, the aluminum sheath on the surface is removed by turning to obtain a hot isostatically pressed aluminum-based composite material containing gadolinium;

[0036] S6, rolling: placing the hot isostatically pressed gadolinium-containing aluminum-based composite material in a muffle furnace, heating it to 450-500°C at a rate of 3-7°C / min, and keeping it warm for at least 1 hour, then rolling it using a two-roll rolling mill, controlling the deformation of a single pass to be 15%-20%, keeping warm for 5-15 minutes after each rolling pass, rolling 4-8 times, and controlling the total deformation to be 50%-90%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

[0037] According to tests, the high-plasticity gadolinium-containing aluminum-based composite material prepared by the present invention has an elongation of 10%-17%, a density greater than 99.5%, a room temperature tensile strength greater than 200 MPa, and a yield strength greater than 140 MPa.

[0038] Figure 1 The MCNP5 software calculation comparison chart of the thermal neutron transmittance of the high-plasticity aluminum-based composite shielding material containing gadolinium at different thicknesses and monoclinic gadolinium oxide additions prepared by the present invention and the thermal neutron transmittance of the aluminum-based composite material containing 30% boron carbide commonly used in industry. Figure 1 It can be seen that at the same thickness, the high-plasticity aluminum-based composite material containing gadolinium prepared by the present invention has a significantly lower neutron transmittance than the aluminum-based composite material containing 30% boron carbide commonly used in industry when the gadolinium addition amount is 10%-15%; even when the gadolinium content is only 5%, its neutron transmittance is similar to that of the aluminum-based composite material containing 30% boron carbide commonly used in industry, and at the commonly used industrial size (3mm thickness), the thermal neutron transmittance does not exceed 0.01%. This shows that the high-plasticity aluminum-based composite shielding material containing gadolinium prepared by the present invention still guarantees a high level of neutron shielding capability on the basis of improved plasticity, density and mechanical properties, and meets the application requirements of neutron shielding devices. Example 1

[0039] A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material comprises the following steps:

[0040] S1, pretreatment of gadolinium oxide powder: weigh 200 g of cubic gadolinium oxide powder with a purity greater than 99.99% and a D50 of 4-5 μm, place it in a muffle furnace, heat it to 1500° C. at a rate of 10° C. / min, and keep it at that temperature for 0.5 h to make it undergo a crystal transformation, and air cool it to room temperature to obtain a monoclinic gadolinium oxide powder with a D50 of 4-5 μm;

[0041] S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, placing the monoclinic gadolinium oxide powder in a high-energy ball mill for ball milling, controlling the mixing mass ratio of the monoclinic gadolinium oxide powder to the stainless steel grinding balls to be 1:1, the ball milling speed to be 300 r / min, the ball milling time to be 12 h, and vacuum drying for 12 h after the ball milling to obtain refined gadolinium oxide powder; Figure 2 (a) is the XRD spectrum of the fine gadolinium oxide powder obtained by ball milling in this example, Figure 2 (b) is a secondary electron microscopic image of the fine gadolinium oxide powder obtained by ball milling in this example. Figure 2 The particle sizes marked in (b) are 1.65 μm, 1.81 μm, 1.82 μm, 1.39 μm, and 2.51 μm from left to upper right. It can be seen that the gadolinium oxide powder after the treatment in steps S1 and S2 is monoclinic, and the particle size D50 is in the range of 1-2 μm;

[0042] S3, composite mixing: the refined gadolinium oxide powder is mixed with 1.8 kg of 6063 aluminum alloy powder with a purity greater than 99.95% and a D50 of 15-25 μm to obtain a mixture, and then the mixture is mixed and ball-milled in an argon atmosphere using a double cone mixer, and the mixing mass ratio of the mixture to the grinding ball is controlled to be 1:1, the ball milling speed is 30 r / min, and the ball milling time is 10 h to obtain a gadolinium oxide / 6063 aluminum composite powder;

[0043] S4, cold isostatic pressing: using a rubber sheath to isolate the hydraulic medium (anti-wear hydraulic oil) from the gadolinium oxide / 6063 aluminum composite powder, and then cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to 100 MPa, and the holding time to 25 minutes, to obtain a cold isostatic pressed ingot;

[0044] S5, hot isostatic pressing sintering: the cold isostatic pressed ingot is placed in a pre-made aluminum package and sintered at 400°C and a vacuum degree of less than 1×10 -3 The hot isostatic pressing sintering process is carried out by heating the sample to 500°C at a rate of 10°C / min, controlling the hot isostatic pressing sintering pressure to 200MPa and the holding time to 2h. After cooling in the furnace, the aluminum sheath on the surface is removed by turning to obtain a hot isostatic pressing aluminum-based composite material containing gadolinium.

[0045] S6, rolling: placing the hot isostatically pressed gadolinium-containing aluminum-based composite material in a muffle furnace, heating it to 480°C at a rate of 5°C / min, and keeping it warm for 1 h, then rolling it using a two-roll rolling mill, controlling the deformation of a single pass to be 15%-20%, keeping warm for 10 min after each rolling pass, rolling 8 times, and controlling the total deformation to be 89%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

[0046] After testing, the density of the 10% Gd2O3 / 6063Al composite material prepared in this embodiment is 99.8%. The cross-sectional microstructure of the composite material is shown in Figure 3 (a)-(c), where (a), (b), and (c) represent the microstructures at different positions on the cross section; the microstructure of the fracture cross section can be found in Figure 4 .from Figure 3-4 It can be seen that the composite material has a dense structure and the reinforcement phase is evenly distributed. The room temperature tensile strength of the composite material is 237 MPa, the yield strength is 175 MPa, and the elongation is 13.5%. Example 2

[0047] A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material comprises the following steps:

[0048] S1, pretreatment of gadolinium oxide powder: placing cubic gadolinium oxide powder with a purity greater than 99.99% and a D50 of 4 μm in a muffle furnace, heating it to 1450° C. at a rate of 5° C. / min, and keeping it at that temperature for 0.3-0.8 h to make it undergo a crystal transformation, and air-cooling it to room temperature to obtain a monoclinic gadolinium oxide powder with a D50 of 3-5 μm;

[0049] S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, placing the monoclinic gadolinium oxide powder in a high-energy ball mill for ball milling, controlling the mixing mass ratio of the monoclinic gadolinium oxide powder to the grinding balls to be 1:2, the ball milling speed to be 300 r / min, the ball milling time to be 10 h, and vacuum drying for 8 h after the ball milling to obtain a refined gadolinium oxide powder with a D50 of 2-3 μm;

[0050] S3, composite mixing: the refined gadolinium oxide powder and the 6063 aluminum alloy powder with a purity greater than 99.95% and a D50 of 15 μm are mixed in a mass ratio of 5:95 to obtain a mixture, and then the mixture is mixed and ball-milled in an argon atmosphere using a double cone mixer, and the mixing mass ratio of the mixture to the grinding ball is controlled to be 1:0.8, the ball milling speed is 25 r / min, and the ball milling time is 10 h to obtain a gadolinium oxide / 6063 aluminum composite powder;

[0051] S4, cold isostatic pressing: using a rubber sheath to isolate the hydraulic medium from the gadolinium oxide / 6063 aluminum composite powder, and then cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to be 150 MPa, and holding the pressure for 15 minutes to obtain a cold isostatic pressed ingot;

[0052] S5, hot isostatic pressing sintering: the cold isostatic pressed ingot is placed in a pre-made aluminum package and sintered at 400°C and a vacuum degree of less than 1×10 -3The hot isostatic pressing sintering process is carried out by heating the sintered aluminum sheet to 485°C at a rate of 5°C / min, controlling the hot isostatic pressing sintering pressure to 150MPa and the holding time to 2h. After cooling in the furnace, the aluminum sheath on the surface is removed by turning to obtain a hot isostatically pressed aluminum-based composite material containing gadolinium.

[0053] S6, rolling: placing the hot isostatically pressed gadolinium-containing aluminum-based composite material in a muffle furnace, heating it to 450°C at a rate of 5°C / min, and keeping it warm for 1.5 hours, then rolling it using a two-roll rolling mill, controlling the deformation of a single pass to be 15%-18%, keeping warm for 5 minutes after each rolling pass, rolling 4 times, and controlling the total deformation to be 50%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

[0054] According to tests, the high-plasticity gadolinium-containing aluminum-based composite material prepared by the present invention has an elongation of 15%, a density of 99.8%, a room temperature tensile strength of 217 MPa, and a yield strength of 152 MPa. Example 3

[0055] A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material comprises the following steps:

[0056] S1, pretreatment of gadolinium oxide powder: placing a cubic gadolinium oxide powder with a purity greater than 99.99% and a D50 of 5 μm in a muffle furnace, heating it to 1600° C. at a rate of 15° C. / min, and keeping it at that temperature for 0.2 h to cause a crystal transformation, and air-cooling it to room temperature to obtain a monoclinic gadolinium oxide powder with a D50 of 5-10 μm;

[0057] S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, placing the monoclinic gadolinium oxide powder in a high-energy ball mill for ball milling, controlling the mixing mass ratio of the monoclinic gadolinium oxide powder to the grinding balls to be 1:2, the ball milling speed to be 400 r / min, the ball milling time to be 15 h, and vacuum drying for 12 h after the ball milling to obtain a refined gadolinium oxide powder with a D50 of 1-2 μm;

[0058] S3, composite mixing: the refined gadolinium oxide powder and the 6063 aluminum alloy powder with a purity greater than 99.95% and a D50 of 25 μm are mixed in a mass ratio of 15:85 to obtain a mixture, and then the mixture is mixed and ball-milled in an argon atmosphere using a double cone mixer, and the mixing mass ratio of the mixture to the grinding ball is controlled to be 1:1.2, the ball milling speed is 35 r / min, and the ball milling time is 24 h to obtain a gadolinium oxide / 6063 aluminum composite powder;

[0059] S4, cold isostatic pressing: using a rubber sheath to isolate the hydraulic medium from the gadolinium oxide / 6063 aluminum composite powder, and then cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to 200 MPa, and holding the pressure for 20 minutes to obtain a cold isostatic pressed ingot;

[0060] S5, hot isostatic pressing sintering: the cold isostatic pressed ingot is placed in a pre-made aluminum package and sintered at 400°C and a vacuum degree of less than 1×10 -3 The hot isostatic pressing sintering process is carried out by heating the sample to 520°C at a rate of 15°C / min, and the hot isostatic pressing sintering pressure is controlled to be 200MPa and the holding time is controlled to be 2h. After the sample is cooled in the furnace, the aluminum sheath on the surface is removed by turning to obtain a hot isostatic pressing aluminum-based composite material containing gadolinium.

[0061] S6, rolling: placing the hot isostatically pressed gadolinium-containing aluminum-based composite material in a muffle furnace, heating it to 500°C at a rate of 5°C / min, and keeping it warm for 2 hours, then rolling it using a two-roll rolling mill, controlling the deformation of a single pass to be 19-20%, keeping warm for 15 minutes after each rolling pass, rolling 7 times, and controlling the total deformation to be 80%-90%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

[0062] According to tests, the high-plasticity gadolinium-containing aluminum-based composite material prepared by the present invention has an elongation of 11%, a density greater than 99.9%, a room temperature tensile strength of 237 MPa, and a yield strength of 161 MPa. Example 4

[0063] The difference between this embodiment and embodiment 1 is that the hot rolling deformation is 60%, and the other conditions are the same.

[0064] The 10% Gd2O3 / 6063Al composite material prepared in this example has a density of 99.6%, a room temperature tensile strength of 205 MPa, a yield strength of 143 MPa, and an elongation of 17%. Example 5

[0065] The difference between this embodiment and embodiment 4 is that the mass of gadolinium oxide is 300 g, the mass of pure aluminum powder is 1.7 kg, and the other conditions are the same.

[0066] The 15%Gd2O3 / 6063Al composite material prepared in this example has a density of 99.7%, a room temperature tensile strength of 220 MPa, a yield strength of 145 MPa, and an elongation of 14%. Example 6

[0067] The difference between this embodiment and embodiment 5 is that the hot rolling deformation is 89%, and the other conditions are the same.

[0068] The 15%Gd2O3 / 6063Al composite material prepared in this embodiment has a density of 99.9%, a room temperature tensile strength of 251 MPa, a yield strength of 190 MPa, and an elongation of 10.5%.

[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a high-plasticity gadolinium-containing aluminum-based composite material, characterized in that: The following steps are involved: S1, pretreatment of gadolinium oxide powder: heating the cubic gadolinium oxide powder to 1200-1800°C at a heating rate of 5-15°C / min, and keeping the temperature for 0.3-0.8h to cause a crystal transformation to obtain a monoclinic gadolinium oxide powder; S2, refining the gadolinium oxide powder: using ethanol as a mixing medium, ball-milling the monoclinic gadolinium oxide powder, and vacuum drying after the ball-milling to obtain a refined gadolinium oxide powder with a D50 of 1-2 μm; S3, composite mixing: the refined gadolinium oxide powder and 6063 aluminum alloy powder are mixed in a mass ratio of (5-15): (85-95) to obtain a mixture, and then the mixture is mixed and ball-milled in an inert gas atmosphere to obtain a gadolinium oxide / 6063 aluminum composite powder; S4, cold isostatic pressing: cold isostatic pressing the gadolinium oxide / 6063 aluminum composite powder, controlling the cold isostatic pressing pressure to be 50-200 MPa, and holding the pressure for 10-40 min to obtain a cold isostatic pressed ingot; S5, hot isostatic pressing and sintering: the cold isostatic pressed ingot is sealed with an aluminum sheath, and then the temperature is raised to 485-520° C. for hot isostatic pressing and sintering, the hot isostatic pressing and sintering pressure is controlled to be 100-200 MPa, and the holding time is 1.5-3 h. After cooling, the aluminum sheath is removed to obtain a hot isostatically pressed aluminum-based composite material containing gadolinium; S6, rolling: heating the hot isostatically pressed gadolinium-containing aluminum-based composite material to 450-500°C and keeping the temperature for at least 1 hour, then rolling, controlling the deformation of a single pass to be 15%-20%, keeping the temperature for 5-15 minutes after each rolling pass, and controlling the total deformation to be 50%-90%, and obtaining the high-plasticity gadolinium-containing aluminum-based composite material after cooling.

2. The method for preparing a high-plasticity gadolinium-containing aluminum-based composite material according to claim 1, characterized in that: The purity of the gadolinium oxide powder in step S1 is greater than 99.99% and the D50 is 4-5 μm; and / or, after the heat preservation in step S1 is completed, the powder is air-cooled to room temperature.

3. The method for preparing a high-plasticity gadolinium-containing aluminum-based composite material according to claim 1, characterized in that: The ball milling in step S2: controlling the mixing mass ratio of monoclinic gadolinium oxide powder to grinding balls to be 1:(0.8-1.2), the ball milling speed to be 250-350 r / min, and the ball milling time to be 10-15 h; and / or, the vacuum drying time in step S2 to be 8-12 h.

4. The method for preparing a high-plasticity gadolinium-containing aluminum-based composite material according to claim 1, characterized in that: The purity of the 6063 aluminum alloy powder in step S3 is greater than 99.95%, and D50 is 15-25 μm; and / or, the ball milling in step S3: controlling the mixing mass ratio of the mixture to the grinding balls to be 1:(0.8-1.2), the ball milling speed to be 25-35 r / min, and the ball milling time to be 10-24 h.

5. The method for preparing a high-plasticity gadolinium-containing aluminum-based composite material according to claim 1, characterized in that: During the cold isostatic pressing in step S4: a rubber sheath is used to isolate the hydraulic medium from the gadolinium oxide / 6063 aluminum composite powder.

6. The method for preparing a high-plasticity gadolinium-containing aluminum-based composite material according to claim 1, characterized in that: The sealing method in step S5 is as follows: the cold isostatically pressed ingot is placed in a prefabricated aluminum package at 350-450°C and a vacuum degree of less than 1×10 -3 Pa; and / or, the heating rate in step S5 is 5-15°C / min; and / or, the cooling method in step S5 is furnace cooling.

7. The method for preparing the high-plasticity gadolinium-containing aluminum-based composite material according to any one of claims 1 to 6, characterized in that: The heating rate in step S6 is 3-7° C. / min; and / or, in step S6, a two-roll rolling mill is used for rolling, and the number of rolling passes is controlled to be 4-8.

8. A high plasticity gadolinium-containing aluminum-based composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The high plasticity gadolinium-containing aluminum-based composite material according to claim 8, characterized in that: Its elongation is 10%-17%, density is greater than 99.5%, room temperature tensile strength is greater than 200MPa, and yield strength is greater than 140MPa.

10. Use of the high-plasticity gadolinium-containing aluminum-based composite material according to any one of claims 8 to 9 in a neutron shielding device.

Citation Information

Patent Citations

  • A black fungus polysaccharide energy gel with anti-fatigue function

    CN105192514B

  • Gadolinium-tungsten element contained aluminum-based composite material and application thereof

    CN110643859A

  • Novel oxide dispersion strengthenedneutron absorption material

    CN109797308A

  • KR20190029219A